Aprendizagem de línguas e léxico: a negociação de significado em práticas telecolaborativas - de Moraes Garcia, Daniela Nogueira [UNESP]; Zakir, Maisa de Alcantara [UNESP]; dos Santos, Gerson Rossi (Editora Unisinos, 2012)
This paper is a qualitative ethnographic study that aims to present reflections on negotiation events in teletandem interactions, a synchronous telecollaborative context of language learning, within the scope of the interaction strategies adopted by participants to achieve comprehensibility. The project Teletandem Brasil: foreign languages for all (Telles, 2006) matches up native or proficient speakers of a foreign language with Brazilian undergraduate students to learn each other's language, by communicating synchronically with application softwares like Skype, Oovoo or MSN. on this paper, based on the interpretive perspective of Hermeneutics, we analyze excerpts of teletandem interactions of partnerships established between students of a Brazilian university and American universities. The excerpts presented here have been taken from different moments of the research studies conducted at the teletandem laboratories of UNESP Assis and Sao Jose do Rio Preto and are part of the database of the works of Santos (2008) and Garcia (2010). In this article, in the data analysis, we highlight the focus on form and on lexicon as characteristics of the interactions and analyze how the negotiations happen in this learning context mediated by technology. Among results we may highlight the prevailing of external feedback as a trigger to negotiation moves, the occurrence of adjustment processes between participants to get adapted to each other's interaction behavior, as well as the evolution of this behavior as interactants get familiarized with the computer-mediated communication context, under the shape of changes in the participants choices regarding negotiation of meaning along their interaction experience.
Language learning and lexicon: meaning negotiation in telecollaborative practices
Keywords: language learning; technology; meaning negotiation